Natural management of napkin rash. - Muggli, R. (European Journal of Pediatric Dermatology, 2009)
Evening primrose oil was investigated in a randomized, open-label, controlled, parallel-group study, for baby skin care and prevention of napkin rash. Sixty-six healthy infants were allocated randomly to treatment with either evening primrose oil or a leading baby skin protection cream. The parents used the supplied test products instead of their conventional skin care product for 8 weeks and kept a diary as to the condition of the skin of the napkin area with respect to type and severity of symptoms of skin irritations. All infants completed the study. No adverse reactions were reported. Medically diagnosed napkin rash was not observed in either group. There was no significant difference between the mean total scores for skin redness, skin rash and skin dryness in the evening primrose oil and the control group. Evening primrose oil could qualify as a safe and natural baby skin care product, as efficacious as currently used ointments or creams for the prevention of napkin rash.